1974
DOI: 10.1021/es60098a003
|View full text |Cite
|
Sign up to set email alerts
|

Trace elements in fly ash. Dependence of concentration on particle size

Abstract: or adsorption onto the smallest particles is proposed to account for the trace element concentration dependence on particle size. The environmental significance of the results is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
310
1
8

Year Published

1975
1975
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 657 publications
(344 citation statements)
references
References 12 publications
(14 reference statements)
20
310
1
8
Order By: Relevance
“…Davison et al (1974) reported a definite trace-element trend with decreasing particle size in fly ash collected from a power plant burning southern Indiana coal. Volatile species such as As, Ni, and Cd all showed an increasing mass fraction with decreasing particle size, and a mechanism of preferential condensation on small particles was proposed to explain the data.…”
Section: Field Studiesmentioning
confidence: 99%
“…Davison et al (1974) reported a definite trace-element trend with decreasing particle size in fly ash collected from a power plant burning southern Indiana coal. Volatile species such as As, Ni, and Cd all showed an increasing mass fraction with decreasing particle size, and a mechanism of preferential condensation on small particles was proposed to explain the data.…”
Section: Field Studiesmentioning
confidence: 99%
“…Of these wastes, especially the fly ashes, cling to the surface of the elements [1][2][3]. These toxic pollutants can leach out and contaminate soils, as well as surface water and groundwater [2,[4][5][6][7][8][9][10][11][12]. Fluidized bed combustion technology is a clean and effective technology to burn coals with high sulphur and ash contents, but with low calorific values.…”
Section: Introductionmentioning
confidence: 99%
“…As the temperature decreases downstream, they may nucleate and grow to form a submicrometer-sized aerosol that is difficult to capture in conventional air-pollution control devices. [1][2][3][4][5][6] Fine particles may pose enhanced health risks; 7 thus, EPA is considering modifying the National Ambient Air Quality Standards for particulate matter. 8 The metallic species have been reported to be enriched in combustion exhausts (compared to their concentrations in the feed).…”
Section: Introductionmentioning
confidence: 99%